I'm currently trying to use Lagrange Multipliers to find the 2 critical points of the function $$ f(x,y,z) = \frac{1}{2}x^{2}+yz+\frac{1}{3} y^{3} - z^{2} $$ subject to $$ h(x,y,z) = x+y+z-2 = 0 $$

I have formed the Lagrangian for this, which is given by $$ L= \frac{1}{2}x^{2}+yz+\frac{1}{3} y^{3} - z^{2} - \lambda (x+y+z-2) $$ and I have worked out that $$ L_{x}= x-\lambda = 0 \\ L_{y}= z+y^{2} - \lambda = 0 \\ L_{z}= y-2z-\lambda = 0 \\ L_{\lambda}=-x-y-z+2 =0 $$

How would I find the values of $x,y,z, \lambda$ that constitute the critical points of this system?

EDIT: I have deduced that $$ x=\lambda \\ y=\frac{4-\lambda}{3} \\ z=\frac{2-2\lambda}{3} $$ Thus, since $x+y+z=2$, we must solve the equation $$ \lambda + \frac{4-\lambda}{3} + \frac{2-2\lambda}{3} = 2 $$ for $\lambda$. However, any $\lambda \in \mathbb{R}$ is a solution.

What am I doing wrong?

  • $\begingroup$ Doing certain correct manipulations you obtained $0=0$. This does not mean that you have done something wrong; it just means that you were not sufficiently aiming at the target. $\endgroup$ – Christian Blatter Dec 9 '15 at 19:12

You got $x$, $y$, and $z$ from below three equations $$\begin{align} L_{x}&= x-\lambda = 0 \\ L_{z}&= y-2z-\lambda = 0 \\ L_{\lambda}&=-x-y-z+2 =0 \end{align}$$ and put those back to one of those ($L_{\lambda}$), which of course always holds.

You should have put those back to this one $$L_{y}= z+y^{2} - \lambda = 0$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.